Genetic Counseling and Germline Testing in the Era of Tumor Sequencing: A Cohort Study. Issue 3 (5th March 2020) - Klek, Stefan; Heald, Brandie; Milinovich, Alex; Ni, Ying; Abraham, Jame; Mahdi, Haider; Estfan, Bassam; Khorana, Alok A; Bolwell, Brian J; Grivas, Petros; Sohal, Davendra P S; Funchain, Pauline
Abstract: Background: The clinical impact of addressing potential germline alterations from tumor-only next-generation sequencing (NGS) is not well characterized. Current guidelines for cancer genetic testing may miss clinically actionable germline changes, which may have important implications for cancer screening, treatment, and prevention. We examined whether increasing involvement of the clinical genetics service during somatic tumor-only NGS review at Molecular Tumor Board (MTB) increases the detection of germline findings. Methods: In a retrospective evaluation of patients who underwent tumor-only NGS and were reviewed at MTB, we quantified genetic counseling (GC) referrals as well as germline testing uptake and results across three cohorts: before (C1) and after (C2) the addition of tumor-only NGS review and after (C3) instituting a formal process to coordinate NGS-based genetics referrals to preexisting oncology appointments. All statistical tests were two-sided. Results: From 2013 to 2017, 907 tumor-only NGS reports were reviewed at MTB (nC1 = 281, nC2 = 493, nC3 = 133); gastrointestinal (22.5%), lung (19.7%), genitourinary (14.8%), and breast (14.1%) were the most common index cancers. GC visits due to MTB increased with each successive cohort (C1 = 1.1%, C2 = 6.9%, C3 = 13.5%; P for trend [ P trend ] < .001), as did germline testing (C1 = 0.7%, C2 = 3.2%, C3 = 11.3%; P trend < .001). Diagnosis of germline pathogenic variants increased with each successive cohort (C1 = 1.4%, C2 = 2.0%, C3 = 7.5%; P trend = .003) and with germline pathogenic variants found by MTB review (C1 = 0.4%, C2 = 0.4%, C3 = 2.3%; P trend = .12). Conclusions: Both review of tumor-only NGS by genetics and the institution of a process coordinating GC with oncology appointments increased the discovery of germline pathogenic variants from tumor-only NGS testing. Furthermore, this process identified germline pathogenic variant carriers who would not have otherwise met standard criteria for germline testing.